Composite membrane, sensor element including said composite membrane, body fat percentage measuring device, electrochemical cell device, and wearable measuring device including said sensor element

By developing a composite membrane containing conductive nanoparticles and hydrolyzable nanofibers, the measurement error problem caused by movement and sweating during use of biosensors is solved, and stable conductivity and mechanical properties are achieved when approaching the human body, improving the reliability and durability of the sensor.

JP7659908B2Active Publication Date: 2025-04-10PUBLIC UNIVERSITY CORPORATION OSAKA CITY UNIVERSITY
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2022542835
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-08-14
Filing Date
2021-07-30
Publication Date
2025-04-10
Estimated Expiration
2041-07-30

AI Technical Summary

Technical Problem

Existing biosensors are prone to measurement errors due to movement and sweating during use, and the instability and production limitations of biomaterials make accurate measurements difficult in close to human environments.

Method used

A composite film containing conductive nanoparticles and hydrolyzable nanofibers has been developed, which has stable conductivity, mechanical strength and flexibility, and can prevent positional displacement and peeling due to changes in humidity when approaching the human body.

Benefits of technology

The composite film maintains stable conductivity and mechanical properties when approaching the human body, reduces measurement errors, and improves the reliability and durability of the sensor due to its reusable conductive nanoparticles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007659908000002
    Figure 0007659908000002
  • Figure 0007659908000003
    Figure 0007659908000003
  • Figure 0007659908000004
    Figure 0007659908000004
Patent Text Reader

Abstract

Provided are: a composite film which has stable electrical conductivity, mechanical strength, and flexibility not readily affected by moisture, and in which position aberration or peeling can be prevented when the composite film is used in close contact with a body to be contacted; a sensor element comprising the composite film, a body fat percentage measuring device, and an electrochemical cell device; and a wearable measuring device comprising the sensor element. A composite film including electroconductive nanoparticles and nanofibers, the nanofibers having a plurality of gaps therebetween that are communicated with the outside, the electroconductive nanoparticles adhering to the surface of the nanofibers and being present in the plurality of gaps, the nanofibers being hydrophilic and biocompatible, and the composite film being electroconductive and being used in close contact with a body to be contacted that is hydrophilic-treated or that contains moisture.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composite membrane, a sensor element including the composite membrane, a body fat percentage measuring device, and an electrochemical cell device, as well as a wearable measuring device including the sensor element. [Background technology]

[0002] In recent years, with the development of biotechnology, attention has been focused on the development of technologies for the evaluation and utilization of biological functions. Each biological function has its own established specificity. Therefore, the development and use of biosensors using non-biological materials such as electronic devices is progressing. Biosensors that can perform analysis quickly, easily, and at low cost are very useful, and applied research using nanotechnology techniques is being actively conducted.

[0003] For example, Patent Document 1 discloses a detection device in which a cell body is filled with a solution of a mixture containing an enzyme body. The detection device of Patent Document 1 detects a target substance by utilizing the molecular recognition function of the enzyme. The electrodes of such biosensors use conductive patterns (electrodes and circuits) that are thin metal films. Generally, conductive patterns are formed as thin metal films on flexible materials using techniques such as screen printing, electroless plating, sputtering, and vapor deposition.

[0004] In addition, Patent Document 2 discloses a composite membrane made of a material containing cellulose nanofibers and metal nanoparticles. However, Patent Document 2 does not disclose a specific embodiment of using the composite membrane as an electrode for evaluating biological functions. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2016-208883 A [Patent Document 2] JP 2018-154921 A Summary of the Invention [Problem to be solved by the invention]

[0006] In order to develop a biosensor that shows excellent characteristics and can easily detect very small amounts of target substances, it is extremely important to develop a material that can be manufactured stably and easily, in addition to improving specificity and sensitivity. For example, electrodes obtained by printing conductive ink on a plastic sheet or the like are useful for acquiring biological information. However, when electrodes are used on a living body, measurement errors occur due to the positional shift of the electrode caused by movement and changes in the amount of sweating. For this reason, it is necessary to develop a system that can correct the deviation of the measurement value caused by sweating, as well as to miniaturize the electrodes. For example, various metabolic products and electrolytes contained in sweat are correlated with blood. For this reason, the development of sensors that target these metabolic products has attracted much attention in the field of wearable devices. In addition, when electrodes are miniaturized, the information acquired by one electrode becomes local. For this reason, when acquiring information over a wide area, it becomes necessary to perform multi-point measurements, and it becomes necessary to take further measures in the design of wearable devices.

[0007] In addition, biological materials generated by living organisms may be unstable or may only be generated in limited environments. In other words, it is preferable to measure biological materials in an environment as close as possible to that of a living organism. Therefore, in order to accurately obtain information from a living organism, electrodes as wearable devices are desirably flexible enough to follow the movements of the living organism, and are also required to have mechanical strength that does not break due to the movements of the living organism. In addition, since electrodes as wearable devices come into direct contact with a living organism, it is desirably breathable and safe for the human body.

[0008] Therefore, the object of the present invention is to provide a composite film that has stable conductivity, mechanical strength, and flexibility that is not easily affected by moisture, and that can prevent displacement or peeling when used in close contact with a contacted body, a sensor element, a body fat percentage measuring device, and an electrochemical cell device that include the composite film, and a wearable measuring device that includes the sensor element. [Means for solving the problem]

[0009] As a result of intensive research into achieving the above object, the present inventors have found that a composite film containing conductive nanoparticles and hydrophilic nanofibers has stable conductivity without being affected by the amount of moisture. The present invention was completed based on these findings.

[0010] That is, the present invention provides a composite membrane comprising conductive nanoparticles and nanofibers, the nanofibers having a plurality of voids between them that communicate with the outside, the conductive nanoparticles attached to the surfaces of the nanofibers and present in the plurality of voids, the nanofibers being hydrophilic and biocompatible, the composite membrane being conductive, and being used in close contact with a contact body that has been subjected to a hydrophilic treatment or contains moisture.

[0011] The amount of the conductive nanoparticles is preferably 2.0 to 20 vol.% relative to the total amount (100 vol.%) of the conductive nanoparticles and the nanofibers.

[0012] The nanofibers preferably contain cellulose.

[0013] The conductive nanoparticles preferably comprise a metal, a metal oxide, or carbon.

[0014] The composite membrane preferably has a tensile strength of 0.5 to 100 MPa.

[0015] The contact object is preferably skin or tissue inside a living body.

[0016] The contacted body preferably comprises metal, glass, plastic, ceramic, or carbon.

[0017] The composite film has flexibility such that when attached to the human body, it deforms or expands and contracts in accordance with the movement of the human body, and it is preferable that the change in resistance value due to the movement of the human body is 2.0 Ω or less.

[0018] It is preferable that the composite membrane has a resistance change of 0.5Ω or less due to an increase or decrease in the amount of liquid present in the plurality of voids.

[0019] The present invention provides a sensor element comprising the above-mentioned composite film and a molecular recognition body disposed in the plurality of gaps.

[0020] The molecular recognition entity preferably includes an enzyme, an antibody, DNA or RNA including an aptamer, an artificial antibody formed from a molecularly imprinted polymer, or an ion-selective molecule.

[0021] Preferably, the enzyme comprises an oxidase, a reductase, or a dehydrogenase.

[0022] The oxidase preferably comprises glucose oxidase or lactate oxidase.

[0023] The dehydrogenase preferably includes glucose dehydrogenase or lactate dehydrogenase.

[0024] The present invention provides a wearable measurement device including the above-mentioned sensor element.

[0025] The present invention provides a body fat percentage measuring device including the above composite membrane.

[0026] The present invention provides an electrochemical cell device comprising the above composite membrane. Effect of the Invention

[0027] The composite film of the present invention has stable conductivity that is not easily affected by moisture, mechanical strength, and flexibility, and can prevent displacement or peeling when used in close contact with a contacted object. In addition, the conductive nanoparticles in the composite film can be easily recovered, allowing for repeated use. [Brief description of the drawings]

[0028] [Figure 1] FIG. 1 is a schematic diagram of a body fat percentage measuring device according to one embodiment of the present invention. [Diagram 2] FIG. 2(A) is a schematic cross-sectional view of a sensor element according to one embodiment of the present invention, and FIG. 2(B) is a schematic cross-sectional view of a conventional sensor element in which an enzyme is immobilized on a flat plate. [Diagram 3] FIG. 3 is an electron microscope photograph of the composite membrane according to Example 2. [Figure 4] FIG. 4(A) is a graph showing the change in water content over time when the composite membrane of Example 3 is immersed in water, and FIG. 4(B) is a graph showing the relationship between the resistance value and the elapsed time when the composite membrane is immersed in water. [Diagram 5] FIG. 5(A) is a graph showing the relationship between the gold concentration in the AuNP / CNF film and the specific resistance, and FIG. 5(B) is a graph showing the relationship between the gold concentration in the AuNP / CNF film and the tensile strength. [Figure 6] FIG. 6(A) is a voltammogram obtained by CV measurement of the composite film of Example 6 in a K3[Fe(CN)6] solution, and FIG. 6(B) is a plot of the peak current value against the gold volume occupancy of the AuNP / CNF film. [Figure 7] FIG. 7 is a voltammogram obtained by CV measurement of the composite membrane of Example 6 in a 0.1M KCl solution. [Figure 8] FIG. 8 shows voltammograms obtained by measuring CV before and after cleaning of the composite membrane of Example 7. [Figure 9] Fig. 9(A) shows the results of CV measurement using the composite membrane of Example 9, Fig. 9(B) is a graph plotting the peak current value against the square root of the sweep rate from the results of Fig. 9(A), Fig. 9(C) shows the results of CV measurement using a gold disk electrode, and Fig. 9(D) is a graph plotting the peak current value against the square root of the sweep rate from the results of Fig. 9(C). [Figure 10] FIG. 10(A) shows the absorption spectrum of a glucose solution measured by the colorimetric method of Reference Example 1, and FIG. 10(B) is a graph plotting the absorbance at 505 nm against the glucose concentration in the measurement cell based on the results of FIG. 10(A). [Figure 11] FIG. 11(A) is a graph of the current response when 25 mM glucose solution was added every minute in Example 11, and FIG. 11(B) is a graph plotting the current value against the concentration based on the results of FIG. 11(A). [Figure 12] FIG. 12(A) is a current response graph when a low concentration of glucose was measured in Example 11, and FIG. 12(B) is a graph in which the current value is plotted against the concentration based on the results of FIG. 12(A). [Figure 13] FIG. 13(A) is a graph showing the current response when each solution of Example 12 was added, and FIG. 13(B) is a graph plotting the current value against the glucose concentration based on the results of FIG. 13(A). [Figure 14] FIG. 14 is a schematic diagram of a two-electrode cell according to Example 13. [Figure 15] FIG. 15(A) is a graph of the current response when the glucose solution of Example 13 was added, and FIG. 15(B) is a graph plotting peak current values ​​against concentration based on the results of FIG. 15(A). [Figure 16] Figure 16(A) is a graph showing the timing of sweat collection in Example 14, Figure 16(B) shows the results of amperometry using sweat before and after a meal, and Figure 16(C) is a graph plotting current values ​​against the time elapsed after a meal. [Figure 17] FIG. 17(A) is a graph showing the current response when the lactic acid solution of Example 17 was added, and FIG. 17(B) is a graph in which the current value is plotted against the concentration based on the results of FIG. 17(A). [Figure 18] FIG. 18(A) is a graph showing the current response when each solution of Example 18 was added, and FIG. 18(B) is a graph plotting the current value against the lactic acid concentration based on the results of FIG. 18(A). [Figure 19] FIG. 19(A) is a graph showing the current response when the lactic acid solution of Example 19 was added, and FIG. 19(B) is a graph in which the current value is plotted against the concentration based on the results of FIG. 19(A). [Figure 20]Figure 20(A) is a photograph of the AuNP / CNF film of Example 20 attached to the palm, and Figure 20(B) is a graph showing the change in resistance of the AuNP / CNF film when the palm is opened and closed every second. [Figure 21] FIG. 21 is a schematic diagram showing one embodiment of a two-electrode cell using the composite membrane of the present invention. [Figure 22] FIG. 22 is a schematic diagram showing another embodiment of a two-electrode cell using the composite membrane of the present invention. [Figure 23] FIG. 23 is a schematic diagram showing one embodiment of a three-electrode cell using the composite membrane of the present invention. [Figure 24] FIG. 24 is a schematic diagram showing another embodiment of a three-electrode cell using the composite membrane of the present invention. [Diagram 25] FIG. 25 is a voltammogram obtained by CV measurement in Example 21. [Figure 26] FIG. 26 is a voltammogram obtained by CV measurement in Example 22. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0029] [Composite membrane] A composite membrane according to one embodiment of the present invention (hereinafter, also simply referred to as a composite membrane) contains conductive nanoparticles and nanofibers, and has electrical conductivity. In the composite membrane, a plurality of nanofibers are, for example, randomly stacked to form a layer. For example, the composite membrane is a nonwoven fabric made of nanofibers. Note that the composite membrane is not limited to a nonwoven fabric, and may be a woven fabric, knitted fabric, or the like formed from yarn containing nanofibers.

[0030] The nanofibers form a plurality of voids between the nanofibers. As a result, the composite membrane has a structure with excellent breathability because it has a plurality of voids that communicate with the outside. In addition, because the voids in the composite membrane allow liquids such as water to enter and exit, the composite membrane can be washed to the inside and can be used repeatedly.

[0031] The composite membrane can be used in a state where it is in close contact with a contacted body that has been subjected to a hydrophilic treatment or that contains moisture. Examples of the contacted body in the state before the hydrophilic treatment of the hydrophilic treatment of the contacted body that has been subjected to the hydrophilic treatment include metal, glass, plastic, ceramic, carbon, etc. When the contacted body is glass, the hydrophilic treatment can be, for example, plasma treatment. When the contacted body is metal, the hydrophilic treatment can be, for example, treatment using a thiol compound. In the treatment using a thiol compound, a solution (such as an aqueous solution) containing a compound having a site capable of forming a bond with the cellulose nanofiber of the composite membrane, such as a thiol group-containing carboxy group, amino group, or hydroxy group, and a site capable of forming a bond with the metal is applied to the metal surface and left to stand. Thereafter, the metal surface may be washed with ultrapure water to remove excess solution. When the contacted body is carbon, examples of the hydrophilic treatment include electrolytic polishing of the contacted body surface in an acid or alkali aqueous solution, or a hydrophilic treatment using an additive such as a surfactant. Since the composite membrane uses hydrophilic nanofibers, it is possible to prevent displacement or peeling when used in close contact with a contacted body that has been subjected to a hydrophilic treatment. By combining the composite membrane with other materials, it can be used as a laminate that also has the properties of the other materials. It is also possible to use the composite membrane by adhering not only one side but both sides to a contact object that has been subjected to a hydrophilic treatment.

[0032] On the other hand, examples of contacted bodies containing moisture include living organisms, wood, plants, etc. The contacted body containing moisture can have the composite film attached to its surface by moisture seeping out from the contacted body itself. When the contacted body is a living organism, the composite film can absorb components seeping out from the surface of the skin into the pores by directly adhering the composite film to the skin, etc. For example, when sweat enters the pores of the composite film, the composite film can be attached to the surface of the skin by expelling the air present in the pores of the composite film. The composite film can also be used inside the body. For example, when the composite film is attached to the palate in the oral cavity, saliva can enter the pores of the composite film and expel the air present in the pores of the composite film, so that the composite film can be attached to the palate. In addition, since the composite film has flexibility, it can be attached to a three-dimensional object such as a human body. This allows the composite film to be attached to an uneven area such as wrinkles on the palm, for example. It is also possible to use the composite film by adhering not only one side but both sides to a contacted body containing moisture. It is also possible to use the composite membrane by bringing one surface of the composite membrane into close contact with a contact object that has been subjected to a hydrophilic treatment, and bringing the other surface of the composite membrane into close contact with a contact object that has been subjected to a hydrophilic treatment.

[0033] The conductive nanoparticles are attached to the surface of the nanofiber. The conductive nanoparticles are bonded to the nanofiber by, for example, hydrogen bonds. When the nanofiber is cellulose, hydrogen bonds are formed between the conductive nanoparticles and the cellulose, for example, via a binder described later. As the binder, a carboxylic acid (salt) is preferable for the purpose of forming the hydrogen bonds by the hydroxyl groups of cellulose, and citric acid (salt) is particularly preferable from the viewpoint of superior biocompatibility. The conductive nanoparticles exist in a state in which they are inserted into the gaps between the nanofibers. When metal nanoparticles are used as the conductive nanoparticles, it is preferable that the metal nanoparticles are arranged in a line so as to be connected along the axial direction of the nanofiber, as shown in FIG. 3 of Example 2 below. When the metal nanoparticles are connected and present along the bundle of nanofibers, the metal conductivity of the composite film is more sufficiently ensured. In other words, when the metal nanoparticles are present in the composite film in a state where they are arranged continuously, electrons can move smoothly between adjacent metal nanoparticles. Therefore, the conductivity of the composite film is ensured with a much smaller amount of metal nanoparticles than when the metal nanoparticles are present uniformly. Even if conductive nanoparticles such as metal oxide or carbon particles are used instead of metal nanoparticles, the same effect can be expected by forming the above-mentioned structure (conductive nanoparticles arranged in a line so as to be connected along the axial direction of the nanofiber).

[0034] The thickness of the composite membrane can be appropriately set depending on the application and the required function, but is preferably, for example, 0.05 to 20 μm. When the thickness of the composite membrane is 0.05 μm or more, sufficient mechanical strength is obtained and the composite membrane has self-supporting property. When the thickness of the composite membrane is 20 μm or less, the composite membrane has sufficient flexibility. The method for measuring the thickness of the composite membrane will be described in detail in Example 4.

[0035] The amount of conductive nanoparticles in the composite film is preferably 2.0 to 20 vol.% relative to the total amount (100 vol.%) of conductive nanoparticles and nanofibers, more preferably 6.0 to 18 vol.%, and even more preferably 10 to 17 vol.%. When the amount of conductive nanoparticles in the composite film is 2.0 vol.% or more relative to the total amount of conductive nanoparticles and nanofibers, sufficient conductivity is obtained. When the amount of conductive nanoparticles in the composite film is 20 vol.% or less relative to the total amount of conductive nanoparticles and nanofibers, sufficient flexibility of the composite film is obtained.

[0036] The resistivity of the composite film is 1×10 -3 It is preferable that the resistance is Ωcm or less, and 1×10 -4 More preferably, it is 1×10 -5 It is more preferable that the resistivity of the composite film is Ωcm or less. The resistivity of the composite film depends on the metal content of the composite film, i.e., the content of the conductive nanoparticles and the composite state. The resistivity of gold used as the conductive material is, for example, 2.44×10 -6 The resistivity of the composite film is 1×10 -3 When the resistivity is Ωcm or less, it is suitable as a conductive material. The method for measuring the resistivity of the composite film will be described in detail in Example 8.

[0037] The composite film preferably has flexibility that allows it to deform or expand and contract with the movement of the human body when it is attached to the human body. This makes it difficult for the composite film to shift or peel off when it is used in close contact with a contacted object. In addition, the change in resistance of the composite film due to the movement of the human body is preferably 2.0Ω or less, more preferably 1.5Ω or less, and even more preferably 1.2Ω or less. By having a change in resistance of 2.0Ω or less, for example, when the composite film is used as an electrode, the obtained current value is less affected by the movement of the human body, so that an accurate value can be obtained. Note that examples of the movement of the human body include opening and closing the palm when the composite film is attached to the palm, and movement of the joint when the composite film is attached to a joint such as the elbow.

[0038] The change in resistance of the composite membrane due to an increase or decrease in the amount of liquid present in the multiple voids is preferably 0.5 Ω or less, more preferably 0.4 Ω or less, and even more preferably 0.3 Ω or less. When the change in resistance is 0.5 Ω or less, for example, when the composite membrane is used as an electrode, the obtained current value is less susceptible to the amount of liquid present in the voids of the composite membrane or the usage environment such as humidity, and therefore an accurate value can be obtained.

[0039] The tensile strength of the composite film is preferably 0.5 to 100 MPa, more preferably 5 to 80 MPa, and even more preferably 10 to 60 MPa. The tensile strength of the composite film depends on the content of conductive nanoparticles in the composite film and the composite state. When the tensile strength of the composite film is 0.5 MPa or more, it is difficult to break and has sufficient durability even when it is used by attaching it to the human body, etc. When the tensile strength of the composite film is 100 MPa or less, it is highly flexible and can deform or expand and contract with the movement of the human body when it is used by attaching it to the human body, etc., so that it is possible to prevent displacement and peeling. The method for measuring the tensile strength of the composite film will be described in detail in Example 4.

[0040] The metallic glossiness (reflectance) of the composite film is not necessarily required. For example, the reflectance of the composite film may be less than 50% of the total reflectance of a pure metal foil. Therefore, the composite film can be easily produced without the need for hot pressing or plating processes to improve the metallic glossiness.

[0041] (Nanofiber) Nanofibers are hydrophilic and biocompatible. In this specification, biocompatibility means that they are not harmful when they come into contact with a living body such as the human body, and safety is maintained. Examples of nanofibers include those made from cellulose, chitosan, chitin, and other polysaccharides. Polysaccharides have many hydroxyl groups in their molecules, so they are compatible with water. Furthermore, these nanofibers have amphiphilicity that also has hydrophobicity, so they show sufficient mechanical strength even when they contain water. Nanofibers are preferably cellulose nanofibers (hereinafter also referred to as CNF) in terms of ease of availability and safety to living bodies. In addition, composite films obtained from cellulose nanofibers have mechanical strength and flexibility. Furthermore, when the conductive nanoparticles are inorganic components such as metal nanoparticles, the cellulose nanofibers can be separated from the conductive nanoparticles by burning them after use. Therefore, the conductive nanoparticles contained in the composite film can be easily recovered and reused after use, and may be used repeatedly.

[0042] The cellulose nanofiber is, for example, made of polysaccharides in which glucose is bound by β-1,4-glycosidic bonds. The cellulose nanofiber is, for example, a fiber having a fiber diameter of 1 to 100 nm. The cellulose nanofiber used in this embodiment is not particularly limited as long as it can be composited with conductive nanoparticles, and examples thereof include known cellulose nanofibers, such as cellulose nanofibers obtained by bacterial synthesis, extracts from natural products such as plants, and processed products thereof. In particular, the former can be obtained as a nanofiber membrane with a desired thickness by setting the synthesis conditions. On the other hand, in the case of the latter, as described in the manufacturing method, a cellulose nanofiber-containing solution can be formed into a nanofiber membrane with a desired thickness by a method such as suction filtration.

[0043] The cellulose nanofiber is preferably a bacterial cellulose nanofiber membrane and a plant-derived cellulose nanofiber because it is easy to synthesize and obtain. As the plant-derived cellulose nanofiber, a commercially available cellulose nanofiber-containing solution as described in the Examples can be used. In the present invention, the cellulose nanofiber contributes to the mechanical properties of the composite membrane. That is, since the mechanical properties of the cellulose nanofiber are utilized, there is no particular need for a fine treatment to make the fiber length and fiber diameter (together, the aspect ratio) uniform, but the mechanical properties of the composite membrane can be controlled with high precision by the aspect ratio. For example, the mechanical strength and flexibility of the composite membrane can be adjusted according to the specifications. In this embodiment, a cellulose nanofiber with a low degree of defibration that becomes cloudy when made into a dispersion solution may be preferably used. The cellulose nanofiber may contain nanofibers other than cellulose as long as the function of the present invention is not impaired.

[0044] (Conductive nanoparticles) In this specification, the term "conductive nanoparticles" refers to particles that have a size on the order of nanometers and are conductive. The order of nanometers includes a range of one to several hundred nanometers, and typically has a particle diameter in the range of 1 to 100 nm.

[0045] The average particle size (median size, D50) of the conductive nanoparticles is not particularly limited, but is preferably 15 to 100 nm, more preferably 15 to 50 nm. When the average particle size of the conductive nanoparticles is 15 nm or more, the compatibility with the cellulose nanofibers is decreased, and the mechanical strength of the composite film is improved. In addition, the amount of the conductive nanoparticles used to obtain sufficient conductivity can be suppressed to a predetermined amount or less. When the average particle size of the conductive nanoparticles is 100 nm or less, the compatibility with the cellulose nanofibers is improved, and the aggregation of the conductive nanoparticles is suppressed to form a uniform composite film. In addition, the amount of the conductive nanoparticles used to obtain sufficient conductivity can be suppressed to a predetermined amount or less. The average particle size of the conductive nanoparticles is a value calculated by the number average, and can be calculated by, for example, measuring the particle sizes of 100 conductive nanoparticles arbitrarily from an image taken using a transmission electron microscope, and averaging the measured values.

[0046] The conductive nanoparticles used in this embodiment are not particularly limited as long as they can be composited with nanofibers, and may be appropriately selected depending on the application and required functions of the composite film. Examples of components constituting the conductive nanoparticles include metals, metal oxides, and carbon. The conductive nanoparticles may be composed of only one type of component, or may contain multiple types of components. Among them, the conductive nanoparticles are preferably particles containing metals as a component (i.e., metal nanoparticles). The metal nanoparticles may be, for example, nanoparticles made of a single element such as gold, silver, palladium, platinum, nickel, copper, iron, lead, lithium, cobalt, manganese, aluminum, zinc, bismuth, silicon, tin, cadmium, indium, titanium, or tungsten, nanoparticles made of multiple elements of these metals, nanoparticles containing oxides or salts of these metals, or nanoparticles containing conductive substances other than metals such as carbon particles. When used by attaching to the human body, the conductive nanoparticles are preferably nanoparticles of a metal selected from, for example, gold, silver, palladium, and platinum. These metal nanoparticles have relatively little effect on the human body and can impart conductivity to the composite film. When the composite film is used in a device such as an electrochemical cell apparatus including a battery or an electrolytic cell, the conductive nanoparticles may be, for example, nanoparticles consisting of a single element such as nickel, copper, iron, lead, lithium, cobalt, manganese, aluminum, zinc, bismuth, silicon, tin, cadmium, indium, titanium, or tungsten, nanoparticles consisting of multiple elements of these metals, nanoparticles containing oxides or salts of these metals, or nanoparticles containing a conductive material other than metals, such as carbon particles, so long as the performance of the device is not affected.

[0047] In particular, gold nanoparticles have little effect on the human body, such as allergies, and therefore the composite film can be safely attached to the skin when used. Therefore, the composite film can be safely used on the skin or tissues inside the living body. Gold nanoparticles can be produced by known methods, for example, the method described in International Publication No. WO2010 / 095574.

[0048] (Application) The composite film is conductive, has high strength, excellent heat resistance and flexibility, is self-supporting, and is easy to mold in a mold or pattern, so it can be expected to be used in new applications such as optical and electronic materials, electrode materials, sensor elements, wearable materials, and electromagnetic wave protection materials. For example, it can be used in body fat measurement devices, etc., as described in detail below. In addition, since it is a material that is safe for living organisms, it can be used not only by sticking it on the surface of the body, but also inside the body, such as the mouth and organs. For example, it can be used as a material used in surgical operations. In addition, by combining it with other materials, it can be used in electrochemical cell devices including batteries or electrolytic cells.

[0049] When the electrochemical cell device is used as a battery or electrolytic cell, the composite membrane functions as a current collector or an electrode. The composite membrane can be directly attached to the inside of a battery or electrolytic cell that has been subjected to a hydrophilic treatment. This allows the battery or electrolytic cell to be made lighter and thinner. In addition, since the composite membrane is directly attached to the battery or electrolytic cell, the composite membrane can be easily arranged, and the manufacturing process is simplified. In addition, since the composite membrane has voids, the surface area is larger than that of a metal thin film. Generally, in an electrochemical cell device, the reaction area in which electrons can move becomes larger as the surface area of ​​the electrode increases. Therefore, when the electrochemical cell device is used as a battery or electrolytic cell, the composite membrane can ensure a large surface area, thereby improving the capacity and reaction efficiency of the battery.

[0050] Examples of the battery or electrolytic cell using the composite membrane include a two-electrode cell and a three-electrode cell. One embodiment of the two-electrode cell and the three-electrode cell is shown in Figs. 21 to 24. The two-electrode cell shown in Figs. 21 and 22 includes a base material 31, and a working electrode 32 and a counter electrode 33 disposed on the base material 31. In the two-electrode cell shown in Figs. 21 and 22, the working electrode 32 is an electrode made of the composite membrane, and is used by impregnating the base material 31 or the working electrode 32 with a liquid electrolyte (not shown). The two-electrode cell shown in Fig. 22 includes a solid electrolyte 35 that electrically connects the working electrode 32 and the counter electrode 33. In Fig. 22, the solid electrolyte 35 covers a part of each of the working electrode 32 and the counter electrode 33, but it may cover the entire base material 31, and it is preferable that the solid electrolyte 35 covers the entire base material 31 except for the part to be attached to the skin. The solid electrolyte 35 is formed as an electrolyte membrane in which a polymer electrolyte membrane or a cellulose nanofiber membrane is impregnated with an electrolyte. By using the above-mentioned electrolyte membrane as an electrolyte, when the two-electrode cell is attached to the skin for use, the solid electrolyte 35 functions as an electrolyte due to moisture in the air, even if the patient does not sweat, and can establish electrical conductivity between the working electrode 32 and the counter electrode 33.

[0051] The three-electrode cell shown in Figs. 23 and 24 includes a base material 31, a working electrode 32, a counter electrode 33, and a reference electrode 36 disposed on the base material 31. In the three-electrode cell shown in Figs. 23 and 24, the working electrode 32 is an electrode made of the above-mentioned composite film. The three-electrode cell shown in Figs. 23 and 24 may also include a solid electrolyte 35 that electrically connects the working electrode 32, the counter electrode 33, and the reference electrode 36. When the solid electrolyte 35 is not used, a liquid electrolyte is used by impregnating, for example, the base material 31 or the working electrode 32. The solid electrolyte 35 preferably covers a part of each of the working electrode 32, the counter electrode 33, and the reference electrode 36, but may cover the entire base material 31, and more preferably covers the entire base material 31 except for the part to be attached to the skin. The solid electrolyte 35 is formed from the above-mentioned electrolyte film. By using the above-mentioned electrolyte membrane as an electrolyte, when the three-electrode cell is attached to the skin for use, the solid electrolyte 35 functions as an electrolyte due to moisture in the air, even if the patient does not sweat, and electrical conductivity can be established between the working electrode 32 and the counter electrode 33.

[0052] Another example of an electrochemical cell device is a biofuel cell. In a biofuel cell, the composite membrane is attached to a current collector such as a metal film. Since the composite membrane has voids, for example, a molecular recognition body can be immobilized. In this embodiment, the molecular recognition body refers to a body that exhibits affinity or selectivity for a specific molecule or a molecule having a specific molecular structure in a part thereof due to intermolecular interactions such as hydrogen bonds, hydrophobic bonds, and van der Waals forces. Examples of molecular recognition bodies include enzymes and microorganisms. The enzymes or microorganisms immobilized in the composite membrane react with a substance in the liquid absorbed in the voids of the composite membrane. For example, when a substance in the liquid is oxidized or reduced by the enzyme or microorganism, electrons are generated in the composite membrane. This allows the biofuel cell to generate an electric current. In addition, since the composite membrane has a large surface area, the reaction area between the enzyme or microorganism and the substance in the liquid is large, and an electric current can be generated efficiently. Furthermore, since the composite membrane is flexible and can be used by being in close contact with the contacted body, the biofuel cell can be used by being attached to the skin of a living body. When the composite membrane is attached to the skin of a living body, sweat and the like exuded from the skin of the living body are absorbed into the voids of the composite membrane. The biofuel cell can generate an electric current by causing an enzyme reaction using a substrate contained in sweat. For example, when lactate dehydrogenase is immobilized on the composite membrane, the lactic acid in the sweat reacts with the lactate dehydrogenase in the composite membrane to generate electrons. This causes the transfer of electrons in the composite membrane, and the biofuel cell can generate an electric current. Note that instead of enzymes, a molecular recognition body according to the target substance, such as an antibody, DNA or RNA containing an aptamer, an artificial antibody formed from a molecularly imprinted polymer, or an ion-selective molecule, can be used. When the target substance is a redox body, the concentration of the target bound to the molecular recognition body can be quantified from the current response in the composite membrane. When the target substance bound to the molecular recognition body is not redox body, the concentration of the target can be electrochemically quantified from the change in potential difference or impedance in the composite membrane. On the other hand, by using these mechanisms, when a certain amount of the target substance is present, it is possible to electrochemically quantify the enzymes, microorganisms, antibodies, DNA or RNA containing aptamers adsorbed on the composite membrane.

[0053] (Method of manufacturing composite membrane) The composite membrane can be obtained, for example, by the following method. When gold nanoparticles are used as the conductive nanoparticles, a dispersion of gold nanoparticles and a dispersion of cellulose nanofibers are mixed to obtain a mixed dispersion of gold nanoparticles and cellulose nanofibers. Cellulose nanofibers disperse well in water. Therefore, they are easily mixed with gold nanoparticles using water as a medium. In this mixed dispersion, the gold nanoparticles and the cellulose nanofibers spontaneously bond with each other through hydrogen bonds. The obtained mixed dispersion is molded by a method such as suction filtration, and the composite membrane can be produced by drying. A known device can be used for drying, and the conditions are not particularly limited as long as the composite membrane is formed without being altered, and are usually in the air at a temperature of 5 to 40°C. In addition, a composite membrane can be produced in the same manner when conductive nanoparticles other than gold nanoparticles are used.

[0054] A cellulose nanofiber membrane or a solid material having a cellulose nanofiber membrane formed on its surface may be immersed in a dispersion of conductive nanoparticles, and conductive nanoparticles may be added to the cellulose nanofiber membrane to obtain a composite membrane. In this case, examples of the cellulose nanofiber membrane include a sheet-shaped cellulose nanofiber membrane and a cellulose fiber structure. The sheet-shaped cellulose nanofiber membrane can be produced by forming a cellulose nanofiber membrane obtained by bacterial synthesis or a cellulose nanofiber-containing solution by a method such as suction filtration. The immersion conditions may be appropriately set depending on the application and required function of the composite planar body to be obtained, but are usually 0.5 to 120 hours in a dispersion at a liquid temperature of 5 to 40°C. In addition, it is preferable to stir the dispersion because the conductive nanoparticles can be added (precipitated) so that they are present in a dispersed state in the cellulose nanofiber membrane. As a result, the conductive nanoparticles can add effects such as improving the conductivity and physical strength to the cellulose nanofiber membrane.

[0055] The dispersion of gold nanoparticles can be prepared as an aqueous solution containing a metal compound containing gold and, optionally, a binder. Examples of the metal compound include tetrachloroauric(III) acid tetrahydrate, chloroauric acid(I), and gold(III) chloride. Examples of the binder include citric acid, sodium citrate, ascorbic acid, sodium ascorbate, potassium carbonate, ammonia, methanol, ethanol, or derivatives and polymers of aniline, pyrrole, and thiophene, molecules having alkyl chains or benzene rings, and molecules having thiol groups, disulfide groups, amino groups, imino groups, carboxy groups, carbonyl groups, etc. at the end or both ends. The binder may be appropriately selected depending on the application and required functions of the composite film to be obtained, but when a sulfur compound is added as a binder, the content of the sulfur compound per 1 g of the composite film can be adjusted to 100 μg or less, or even 10 μg or less, which is preferable. In addition, when no binder is used or when a binder that does not contain sulfur is used, a sulfur-free composite film can be obtained.

[0056] The concentration of the metal compound in the dispersion is 1×10 -5 ~1×10 -1 The mass ratio of the cellulose nanofibers to the metal in the metal compound is about 1:0.1-3.

[0057] The method for producing a composite membrane may further include a step of hot pressing the composite membrane. The hot pressing can be performed using a known device, and the set temperature, pressure, and time can be appropriately set depending on the application and the required function. Specifically, since the heat resistance temperature of cellulose nanofiber is about 350°C, the sheet-shaped composite membrane of conductive nanoparticles / cellulose nanofibers is hot pressed at 100°C to 350°C and 10MPa to 40MPa. The processing time is about 1 to 10 minutes. When the conductive nanoparticles are metal nanoparticles, the surface of the composite membrane becomes smooth by hot pressing, the metallic glossiness (reflectance) is improved, the filling rate and contact rate of the metal nanoparticles are increased, and a network in which a conductive path formed by connecting a plurality of metal nanoparticles spreads in a planar shape is formed. Therefore, although it depends on the metal content, the conductivity becomes equivalent to the resistivity of the pure metal of the metal nanoparticles. For example, even if the amount of gold used in the conventional gold foil is reduced to a volume occupancy rate of 20% or less, a highly conductive composite membrane can be formed.

[0058] When the conductive nanoparticles are metal nanoparticles, the method for producing a composite film may further include a step of growing the metal nanoparticles in the composite film. This can be done by putting the composite film with the metal nanoparticles fixed into a dispersion liquid containing the metal nanoparticles and stirring. This allows the metal nanoparticles to grow as the metal nanoparticles in the dispersion liquid adhere to the surfaces of the metal nanoparticles in the composite film. Alternatively, the metal salt or metal complex in the dispersion liquid containing the metal nanoparticles is reduced and precipitated using the metal nanoparticles of the composite film as nuclei, allowing the metal nanoparticles to grow.

[0059] The method for producing the composite membrane may include a step of washing the inside of the composite membrane with ultrapure water (washing step) after the composite membrane is formed. This makes it possible to remove excess salts and the like that have entered the gaps between the nanofibers in the composite membrane during production. The method for producing the composite membrane will be described in detail in Example 1. The following describes a body fat percentage measuring device and a sensor element that use the composite membrane.

[0060] [Body fat percentage measuring device] Fig. 1 is a schematic diagram of a body fat percentage measurement device according to one embodiment of the present invention. As shown in Fig. 1, the body fat percentage measurement device 10 includes a composite membrane 11, an AC power supply device 12, and an impedance measurement unit 13. The impedance measurement unit 13 is built into the AC power supply device 12. The impedance measurement unit 13 may be configured independent of the AC power supply device 12. The composite membrane 11 is connected to the AC power supply device 12 and the impedance measurement unit 13. The AC power supply device 12 applies a sine wave current with a frequency of 50 kHz and a current value of 1.0 mA to the composite membrane 11. The impedance measurement unit 13 detects the impedance of the composite membrane 11.

[0061] In the body fat percentage measuring device 10, the composite membrane 11 is used as an electrode. The composite membrane 11 is used in a state where it is attached to the skin and in close contact with it. In this specification, "close contact" means that at least a part of the contacted body is in close contact with it, and it is not necessary that the entire composite membrane 11 is in close contact with the contacted body. For example, the subject attaches the composite membrane 11 to the heels of both feet and stands upright on the ground to measure the body fat percentage. Note that the location where the composite membrane 11 is attached is not limited to the heels of both feet, and it may be attached to the palms, for example.

[0062] It is preferable to calculate the body fat percentage by the bioelectrical impedance method because it is simple and quick. The bioelectrical impedance method is a method for estimating body composition by passing a weak current through the body and measuring the resistance at that time. In the body, tissues that contain a lot of electrolytes such as water, such as muscles, have the property of conducting electricity well, while fat tissues have the property of not conducting electricity well. For this reason, the resistance value of the body increases as the amount of fat in the body increases. The bioelectrical impedance method utilizes this property to calculate the body fat percentage.

[0063] First, the body density (BD) is calculated from the subject's height (Ht), weight (W), and the obtained impedance (BI) using the following formula (1). Next, the obtained body density (BD) is substituted into Brozek's formula (formula (2)) to calculate the body fat percentage. BD [g cm -3 ]=1.1278-0.115×W×BI / Ht2 +0.000095·BI···Equation (1) Body fat percentage [%]=(4.971 / BD-4.519)×100...Equation (2) (W: weight [kg], BI: impedance [Ω], Ht: height [cm])

[0064] The body fat percentage measuring device 10 has a composite membrane 11. The composite membrane 11 can be in close contact with the body of the subject. As will be described in the examples, the dielectric constant of the composite membrane 11 does not change with changes in water content and shape. For this reason, it is presumed that the body fat percentage measuring device 10 can measure a more accurate body fat percentage than conventional products.

[0065] [Sensor element] FIG. 2(A) is a schematic cross-sectional view of a sensor element (hereinafter, also referred to as sensor element 20) according to one embodiment of the present invention. The sensor element 20 further includes a molecular recognition body 22 in the composite membrane 11. The molecular recognition body 22 may be a holoenzyme containing a coenzyme. The molecular recognition body 22 has a size of about 5 to 30 nm. As shown in FIG. 2(A), the molecular recognition body 22 is disposed in a plurality of voids 23 of the composite membrane 11, that is, between the cellulose nanofibers. Although not shown, conductive nanoparticles are present on the surface of the composite membrane 11 including the voids 23. The conductive nanoparticles impart effects such as improving the conductivity or physical strength to the composite membrane 11. Furthermore, the molecular recognition body 22 is interspersed between the conductive nanoparticles.

[0066] When the molecular recognition body 22 is an enzyme, it exhibits specific enzyme activity for a specific substance (hereinafter, also referred to as substrate 24). The sensor element 20 utilizes a chemical reaction caused by the catalyst of the molecular recognition body 22, which is an enzyme. For example, when the substrate 24 undergoes an oxidation reaction or a reduction reaction due to the molecular recognition body 22, electrons are transferred between the substrate 24 and the conductive nanoparticles of the composite film 11 directly via a coenzyme (not shown) or indirectly via an electron mediator (not shown). Electrons are transferred through the molecular recognition body 22 and the conductive nanoparticles in the composite film 11 in proportion to the amount of chemical reaction. Therefore, a current is generated through the composite film 11 according to the amount of electron transfer. That is, a current is generated based on the electrochemical reaction of the product generated by the reaction between the molecular recognition body 22 and the substrate 24. As a result, the enzyme sensor using the sensor element 20 can measure the amount of the substrate 24 contained in the sample that comes into contact with the sensor element 20.

[0067] The molecular recognition body 22 is preferably, for example, an oxidase, a reductase, a dehydrogenase, or a holoenzyme containing a coenzyme. When the molecular recognition body 22 is a holoenzyme, the coenzyme is preferably flavin adenine dinucleotide or nicotine adenine dinucleotide, or pyrroloquinoline quinone. When the molecular recognition body 22 is an oxidase, the enzyme sensor using the sensor element 20 can measure the amount of the substrate 24 contained in the sample by oxidizing the substrate 24. When the molecular recognition body 22 is a reductase, the enzyme sensor using the sensor element 20 can measure the amount of the substrate 24 contained in the sample by reducing the substrate 24.

[0068] The oxidase is preferably glucose oxidase or lactate oxidase. Thus, an enzyme sensor using the sensor element 20 can measure the concentration of glucose or lactate contained in, for example, human sweat. For example, glucose oxidase causes an enzymatic reaction between a substrate glucose and dissolved oxygen to produce gluconolactone and hydrogen peroxide. Lactate oxidase causes an enzymatic reaction between a substrate lactic acid and dissolved oxygen to produce pyruvic acid and hydrogen peroxide. Hydrogen peroxide can be electrochemically detected using an Ag|AgCl electrode at +0.6 V. Therefore, the concentration of glucose or lactate can be quantified from the current response accompanying the generation of hydrogen peroxide.

[0069] In addition, as the molecular recognition body 22, a so-called holoenzyme, which is a complex of an enzyme and a coenzyme, may be used at appropriate times. Also, an electron mediator molecule may be added to the composite film 11, and the electron mediator molecule may be immobilized on the surface of a cellulose nanofiber or a conductive nanoparticle by using a covalent bond or a bond via a thiol. The coenzyme or electron mediator molecule has a function of transporting electrons by repeatedly undergoing an oxidation-reduction reaction by itself. In general, as the coenzyme, flavin adenine dinucleotide, nicotine adenine dinucleotide, or pyrroloquinoline quinone is used. As the electron mediator, a substance having a reversible oxidation-reduction property, such as hexacyanoferric (III) ion, hexacyanoferric (II) ion, a ferrocene derivative, or a quinone compound, may be used. The action of the coenzyme or electron mediator makes it possible to improve the response and speed of the measurement without being affected by dissolved oxygen.

[0070] Although the case where an enzyme is used as the molecular recognition body 22 has been described, the molecular recognition body 22 is not limited to an enzyme. The molecular recognition body 22 may be, for example, an antibody that selectively binds to a target substance, DNA or RNA containing an aptamer, an artificial antibody formed from a molecular imprinted polymer, or an ion-selective molecule. When the target substance is a redox product, the concentration of the target bound to the molecular recognition body 22 can be quantified from the current response in the composite membrane 11. When the target substance bound to the molecular recognition body 22 is not redox product, the concentration of the target can be electrochemically quantified from the change in potential difference or impedance in the composite membrane 11.

[0071] FIG. 2(B) is a schematic cross-sectional view of a sensor element 50 in which a molecular recognition body 22 is fixed to a conventional flat plate electrode 51. When the molecular recognition body 22 is an enzyme, as shown in FIG. 2(B), when the molecular recognition body 22, which is an enzyme, is fixed to the flat plate electrode 51, the molecular recognition body 22 is fixed facing various directions on the flat plate electrode 51. The enzyme has a recognition part 21 that recognizes a substrate. When the recognition part 21 side is fixed to a position relatively close to the flat plate electrode 51 without being covered by the flat plate electrode 51 as in the molecular recognition body 221 shown in FIG. 2(B), when electrons move in the recognition part 21, the electrons are smoothly transmitted to the flat plate electrode 51. However, when the recognition part 21 side is fixed to be covered by the flat plate electrode 51 as in the molecular recognition body 222 shown in FIG. 2(B), the recognition part 21 side cannot recognize the target substance. 2(B), when the recognition unit 21 is fixed facing away from the plate electrode 51, the distance between the recognition unit 21 and the plate electrode 51 becomes long. Therefore, even if an electron moves in the recognition unit 21, the electron may not be transmitted to the plate electrode 51. Therefore, in a sensor element 50 in which the molecular recognition unit 22 is fixed to the plate electrode 51, the molecular recognition unit 22 may not be fully utilized or the electron movement may not be detected depending on the orientation of the molecular recognition unit 22.

[0072] In contrast, the composite membrane 11 has various voids 23 communicating with the outside. The molecular recognition body 22 is disposed in the voids 23. The wall surface of the composite membrane 11 forming the voids 23 has a complex shape compared to a flat surface. Therefore, even if the molecular recognition body 22 has various orientations with respect to the composite membrane 11, as shown in FIG. 2(A), the recognition unit 21 side is often fixed to a position relatively close to the composite membrane 11 without being covered by the composite membrane 11. Therefore, the sensor element 20 can fully utilize the molecular recognition body 22 regardless of the orientation of the molecular recognition body 22, and can smoothly detect the transfer of electrons. Therefore, even if the amount of substrate contained in the sample is small, the enzyme sensor using the sensor element 20 is presumed to be able to measure with high accuracy because the reaction occurs more efficiently than the enzyme sensor using the plate electrode 51. For example, even if the enzyme sensor using the sensor element 20 is used as a wearable measurement device and is used in close contact with a living body, it can measure the concentration of a small amount of glucose or lactic acid contained in human sweat. In addition, since the composite membrane 11 has a structure having a large number of voids 23, sweat permeates into the voids 23. Therefore, the composite membrane 11 can efficiently measure a trace amount of glucose or lactic acid in a solution.

[0073] The sensor element 20 is obtained by fixing the molecular recognition body 22 to the composite membrane 11 by a known method. For example, the molecular recognition body 22 is fixed to the cellulose nanofiber in the composite membrane 11 by a covalent bond, a bond via a thiol, or an electrostatic interaction. The sensor element 20 may include a single molecular recognition body 22, or may include multiple types of molecular recognition bodies 22. The method for producing the sensor element will be described in detail in Examples 10 and 16. EXAMPLES

[0074] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples, and modifications and improvements within the scope of the present invention that can achieve the object of the present invention are included in the present invention. The ultrapure water used in this example was filtered, pH adjusted, passed through a reverse osmosis membrane and an ion exchange membrane, and sterilized with ultraviolet light. All the reagents used in this example were of special grade, and unless otherwise stated, reagents from Fujifilm Wako Pure Chemical Corporation were used.

[0075] Preparation Example 1 Preparation of Gold Nanoparticle Dispersion 12 mL of 1 wt% aqueous solution of chloroauric(III) acid tetrachloride and 9 mL of 2 wt% aqueous solution of sodium citrate were added to 400 mL of ultrapure water, and the mixture was stirred at 80°C for 20 minutes using a stirrer to obtain a gold nanoparticle dispersion (average particle size 30 nm, 0.0136 wt%).

[0076] Example 1 Preparation of Composite Membrane 250 mL of the above gold nanoparticle dispersion was added to 0.5 g of 2 mass% cellulose solution (biomass nanofiber Binfis IMa-10002, manufactured by Sugino Machine Co., Ltd.), and stirred for 1 minute at room temperature using a stirrer to obtain a gold nanoparticle / cellulose nanofiber (hereinafter, gold nanoparticle / cellulose nanofiber is also referred to as AuNP / CNF). The AuNP / CNF mixed dispersion was subjected to suction filtration for 5 minutes using a suction filtration device (manufactured by Merck Millipore Co., Ltd.) equipped with a PTFE membrane filter (Omnipore membrane filter, pore size 1 μm, manufactured by Merck Millipore Co., Ltd.), and the AuNP / CNF mixture was precipitated on the membrane filter. The AuNP / CNF mixture was removed together with the membrane filter, placed on a hot plate (C-MAG HP10, IKA), and dried by heating at 130°C for 2 minutes. The composite film (hereinafter also referred to as the AuNP / CNF film) was then peeled off from the membrane filter to obtain an AuNP / CNF film (gold: 13 vol.%). The obtained AuNP / CNF film was self-supporting and flexible. Since the filtrate obtained by filtration was colorless and transparent, it is presumed that all of the gold nanoparticles in the gold nanoparticle dispersion remained in the AuNP / CNF mixture on the membrane filter.

[0077] Example 2 <Surface observation of AuNP / CNF membrane> The surface of the AuNP / CNF film (gold: 13 vol.%) was observed using a scanning electron microscope (SEM, Miniscope (registered trademark), TM3030, Hitachi High-Technologies Corporation). A top view photograph is shown in Figure 3.

[0078] It was confirmed from Figure 3 that the AuNP / CNF film has many voids. In addition, the white particles with a diameter of about 30 nm shown in Figure 3 are gold nanoparticles, and the thread-like objects with a diameter of about 100 nm are cellulose nanofibers. It is believed that the gold nanoparticles are attached to the cellulose nanofibers by hydrogen bonds formed between the carboxyl group of citric acid, which is the protective group of the gold nanoparticles, and the hydroxyl group of cellulose.

[0079] Example 3 <Water content and resistance measurement of AuNP / CNF membrane> The AuNP / CNF membrane (gold: 13 vol.%) was immersed in ultrapure water for a specified time. The weight of the AuNP / CNF membrane was measured before and after immersion, and the resistance value was measured with a digital multimeter (34410A, Agilent Technologies, applied current: 1 mA). The results are shown in Figure 4(A) and Figure 4(B). Figure 4(A) is a graph showing the change in water content over time when the AuNP / CNF membrane was immersed in water, and (B) is a graph showing the relationship between time and resistance value when the AuNP / CNF membrane was immersed in water.

[0080] As shown in Figure 4(A), the weight of the AuNP / CNF membrane was 2.5 times that of the membrane immediately after immersion in ultrapure water 120 minutes after immersion, and no significant change was observed thereafter. In addition, as shown in Figure 4(B), the resistance value of the sample at each time was low, less than 1Ω, regardless of the water content, and the variation in the measured values ​​was less than 0.5Ω. In other words, in the AuNP / CNF membrane (gold: 13 vol.%), the change in resistance value due to the increase or decrease in the amount of liquid present in the multiple voids was less than 0.5Ω. Furthermore, when the AuNP / CNF membrane was thoroughly dried after this evaluation experiment and the resistance value was measured again, the resistance value was 0.76Ω. From this, it was confirmed that the resistance value of the AuNP / CNF membrane was not affected even when it contained water, and it maintained high conductivity even in solution, and it can be used as an electrode.

[0081] Example 4 <Resistance and tensile strength as a function of gold concentration in AuNP / CNF membrane> In the preparation example of the gold nanoparticle dispersion, multiple AuNP / CNF films with different gold concentrations were prepared in the same manner as in Example 1, except that only the gold concentration was changed. The specific resistance value of the AuNP / CNF film was measured using a digital multimeter (34410A, manufactured by Agilent Technologies, Inc., applied current: 1 mA) and an ultra-high resistance / microcurrent meter (8340A, manufactured by ADC Corporation). The results are shown in FIG. 5(A). In addition, the tensile strength of the AuNP / CNF film (6.6 vol.%, 11.0 vol.%, 13.0 vol.%, 17.0 vol.%), CNF film, and gold foil was measured. The results are shown in FIG. 5(B). The tensile strength of the AuNP / CNF film and CNF film was measured at 25°C by cutting each film into 2 x 2 cm and using a digital force gauge (FJGN-50, manufactured by Nidec-Shimpo Corporation). The thickness of the AuNP / CNF film, which was also measured similarly for gold foil (99.95%, AU-173174, manufactured by Nilaco Corporation), was measured using a scanning electron microscope (SEM, TM3030, manufactured by Hitachi High-Technologies Corporation).

[0082] As shown in Figure 5(A), the resistivity of the AuNP / CNF film gradually decreased with increasing gold content in the film, and then decreased sharply when the gold content was 6 vol%. In addition, when the gold content was 13 vol%, the resistivity of the AuNP / CNF film was equivalent to that of a gold plate (2.9 × 10 -6 The AuNP / CNF film had a thickness of 5-10 μm and, while flexible, exhibited a tensile strength more than five times higher than that of a gold plate, as shown in Figure 5(B).

[0083] Example 5 <Preparation of electrodes using AuNP / CNF membrane> AuNP / CNF membrane (AuNP / CNF membranes with gold content of 2.5 vol.% to 17.0 vol.% (2.5 vol.%, 3.8 vol.%, 5.7 vol.%, 6.4 vol.%, 6.6 vol.%, 11.0 vol.%, 13.0 vol.%, 17.0 vol.%) were prepared in the same manner as in the preparation of the above composite membrane.) was cut into a circle with a diameter of 1 cm, and a part of it was sandwiched between Teflon (registered trademark) tape cut into a circle with a diameter of 6 mm. A gold wire was connected to the AuNP / CNF membrane as a lead wire to obtain an AuNP / CNF membrane electrode.

[0084] Example 6 <Cyclic voltammetry (CV) measurement> A 0.1M KCl aqueous solution and a 5mM K3[Fe(CN)6] solution prepared with a 0.1M KCl aqueous solution were prepared as electrolytes. AuNP / CNF membrane electrodes (gold: 3.8vol.%, 5.7vol.%, 6.4vol.%, 6.6vol.%, 11.0vol.%, 13.0vol.%, 17.0vol.%) were used as working electrodes, Ag|AgCl electrodes as reference electrodes, and Pt coil electrodes as counter electrodes, and each was immersed in the electrolyte. Cyclic voltammetry (ALS842B, BAS Inc.) was used to measure the potential at 50mVs -1 CV measurements were performed at a sweep rate of 100 s. The results of CV measurements in a 5 mM K3[Fe(CN)6] solution are shown in Figure 6(A). Figure 6(B) shows the peak current value plotted against the gold volume occupancy of the AuNP / CNF membrane. Note that Figure 6(A) does not show the measured value for the AuNP / CNF membrane electrode with a gold concentration of 3.8 vol.%.

[0085] From the voltammogram shown in Figure 6(A), a typical response based on the oxidation-reduction of ferricyanide was observed when the amount of gold in the AuNP / CNF film was 6.4 vol.% or more. From Figure 6(B), when the amount of gold in the AuNP / CNF film was 11 vol.% or more, no change was observed in the peak current value. In addition, the results of CV measurement in 0.1M KCl solution are shown in Figure 7. From Figure 7, it was confirmed that the background increases with the increase in the amount of gold in the AuNP / CNF film.

[0086] Example 7 Effects of washing the AuNP / CNF membrane To remove potential surface contaminants, the following procedure was performed, and CV measurements were taken before and after the procedure. A 0.1M H2SO4 aqueous solution was prepared as the electrolyte. The AuNP / CNF membrane electrode (gold: 13 vol.%) was immersed in the electrolyte as the working electrode, the Ag|AgCl electrode as the reference electrode, and the Pt coil electrode as the counter electrode. A cyclic voltammetry (ALS842B, manufactured by BAS Co., Ltd.) was used for the cleaning procedure, and the CV measurements were taken before and after the procedure. -1 CV measurements were performed for 100 revolutions at a sweep rate of 50 mVs. Before and after the CV measurements, CVs were performed in a 5 mM FeCl3 solution dissolved in a 0.1 M H2SO4 solution. The sweep rate was 50 mVs. -1 The results are shown in Figure 8.

[0087] Comparing the voltammograms before and after cleaning, there was almost no change in the magnitude of the charging current, as shown in Figure 8. Therefore, it is speculated that the change in charging current is not due to contamination of the AuNP / CNF film, but rather that the structure of the AuNP / CNF film itself is the factor that generates the charging current.

[0088] Example 8 <Evaluation of chemical resistance of AuNP / CNF membrane> The following operations were performed to evaluate the chemical resistance of the AuNP / CNF membrane. The AuNP / CNF membrane was placed in a Falcon tube filled with various treatment solutions and soaked. The various treatment solutions used were HCl (1M), NaOH (1M), ethanol, toluene, and 5% neutral detergent. The soaked AuNP / CNF membrane was treated with ultrasound (45 kHz) for 30 minutes. The resistivity of the AuNP / CNF membrane was measured with a digital multimeter (34410A, Agilent Technologies, Inc., applied current: 1 mA). The membrane was placed on a pair of electrodes (0.3 mm) with a gap of 3 mm using a 3 mm gap, and the resistivity was calculated as the average value of the electrical resistance measured three times at 25 °C. The membrane thickness was set to 50 nm. The absorption spectra of the solutions before and after treatment were measured and compared. 3 mL of each solution before and after treatment was placed in a cell for measuring the absorption spectrum, and the absorption spectrum was measured using a UV-visible spectrophotometer (V-750, JASCO).

[0089] No change was observed in the resistivity of the AuNP / CNF film or the absorption spectrum of the solution before and after treatment. Therefore, there was no outflow of gold nanoparticles to each chemical, and it is presumed that the gold nanoparticles are not only chemically attached but are also surrounded by the cellulose nanofibers, making them physically difficult to release.

[0090] Example 9 Electrochemical characterization of AuNP / CNF films A 5 mM K3[Fe(CN)6] solution prepared with 0.1 M KCl aqueous solution was prepared as the electrolyte. A AuNP / CNF membrane electrode (gold: 13 vol.%) or a gold disk electrode was used as the working electrode, an Ag|AgCl electrode was used as the reference electrode, and a Pt coil electrode was used as the counter electrode. Each electrode was immersed in the electrolyte. A cyclic voltammetry (ALS842B, manufactured by BAS Co., Ltd.) was used to measure the potential difference between 5 and 50 mVs. -1CV measurements were performed at a sweep rate of 1000 s. The results are shown in Figure 9(A) and Figure 9(B). Figure 9(A) shows the results of CV measurements using an AuNP / CNF membrane electrode, and Figure 9(B) is a graph plotting the peak current value against the square root of the sweep rate from the results of Figure 9(A). Figure 9(C) shows the results of CV measurements using a gold disk electrode, and Figure 9(D) is a graph plotting the peak current value against the square root of the sweep rate from the results of Figure 9(C).

[0091] As shown in Figures 9(A) and 9(C), the AuNP / CNF membrane electrode showed the same redox peak as the gold disk electrode. In addition, an increase in the peak current value was observed with an increase in the sweep rate. At this time, the peak separation of each electrode was calculated to be 73 mV for the AuNP / CNF membrane electrode and 64 mV for the gold disk electrode. Both values ​​were close to the theoretical value of 57 mV for a one-electron transfer reaction, and it was confirmed that the reaction was a general reversible system. In addition, when the peak current value was plotted against the square root of the sweep rate, a straight line was drawn based on the theoretical formula for the peak current (Equation (3) below), as shown in Figures 9(B) and 9(D), and it was confirmed that this system was a reversible process dominated by diffusion.

[0092] In addition, the diffusion coefficient D was calculated from the voltammogram obtained when a gold disk electrode was used as the working electrode, and was found to be 3.9 × 10 -6 cm 2 By substituting this value into the following formula (3), the area of ​​the AuNP / CNF membrane electrode was calculated to be 0.36 cm 2 This was calculated based on the geometric area of ​​the AuNP / CNF membrane electrode (0.28 cm 2 ) was approximately 1.3 times larger than that of the AuNP / CNF membrane. Therefore, it is believed that the surface area is increased due to the particulate nature of the many gold nanoparticles present on the AuNP / CNF membrane surface. Ip(peak current)=269n 3 / 2 AD 1 / 2 Cv 1 / 2 (3) (wherein n is the reaction quantum number, A is the electrode area cm 2 , D: diffusion coefficient cm 2 / S, C: concentration in mol / L, v: sweep speed (V / s).

[0093] Reference example 1 (Quantification of glucose concentration by colorimetry) Hereinafter, a colorimetric method for determining a glucose solution using the glucose oxidase / peroxidase (GOD / POD) method will be described as a reference example.

[0094] A staining reagent was prepared using Labo Assay (registered trademark) glucose. 4-aminoantipyrine and phenol were used as the staining reagent. 20 μL of a predetermined concentration of glucose (2.8 mM to 0.3 M) was mixed with 3 mL of the staining reagent and reacted in a thermostatic bath (37 ° C) for 5 minutes. Glucose oxidase reacts glucose with dissolved oxygen to produce gluconolactone and hydrogen peroxide. Aminoantipyrine and phenol are oxidatively condensed in the presence of peroxidase and hydrogen peroxide to produce a red quinone pigment. 3 mL of each solution after the reaction was placed in a cell for measuring the absorption spectrum, and the absorption spectrum was measured using a UV-visible spectrophotometer (V-750, manufactured by JASCO). At this time, the coloring reagent was used as a control, and the measurement range was set to 300 to 800 nm. The results are shown in FIG. 10 (A). Figure 10(B) is a graph plotting the absorbance at 505 nm against the glucose concentration in the measurement cell based on the results of Figure 10(A). The figure in Figure 10(B) is a graph plotting the absorbance at 505 nm against the glucose concentration dropped.

[0095] The absorbance of this red dye at 505 nm is proportional to the concentration of hydrogen peroxide. Therefore, the glucose concentration is quantified based on the magnitude of absorbance. As shown in FIG. 10(A), it was confirmed that the peak of absorbance at 505 nm becomes larger as the glucose concentration increases. As shown in FIG. 10(B), it can be seen that the glucose concentration can be quantified in the concentration range of 0.002 mM to 0.5 mM. As shown in FIG. 10(C), it can be seen that the glucose concentration can be quantified in the concentration range of 0.3 mM to 75 mM. It should be noted that the quantitative determination of high concentrations of glucose can be obtained using the calibration curve obtained from the graph in FIG. 10(C), but the sample must be diluted.

[0096] Example 10 Preparation of glucose sensor 240 U / mg of glucose oxidase (hereinafter referred to as GOD) derived from Aspergillus niger was immobilized on the AuNP / CNF membrane electrode by the glutaraldehyde crosslinking method. In conjunction with the immobilization, a mixture of GOD, bovine serum albumin (hereinafter referred to as BSA), and glutaraldehyde (hereinafter referred to as GA) was prepared. The method for preparing the mixture is as follows. (1) Weigh out approximately 5 mg of GOD and add 12 UμL -1 A GOD solution was prepared by dissolving the GOD in 0.2 M phosphate buffer (pH 7.0) so that the GOD concentration became (2) Weigh out approximately 11 mg of BSA and dilute it to 110 mg mL -1 A BSA solution was prepared by dissolving the BSA in 0.2 M phosphate buffer (pH 7.0) so that the concentration became (3) A GA solution was prepared by dissolving the 25% GA solution in 0.2 M phosphate buffer (pH 7.0) to a concentration of 7%. (4) 3 μL of the GOD solution from (1), 29 μL of the BSA solution from (2), and 4 μL of the GA solution from (3) were mixed to obtain a total of 36 μL of a mixed solution. 6 μL (6 U) of the mixed solution was dropped onto the AuNP / CNF membrane electrode (gold: 13 vol.%). The mixture was left to stand in the dark for 24 hours to obtain a glucose sensor. The glucose sensor was then stored in 0.2 M phosphate buffer (pH 7.0).

[0097] Example 11 Glucose sensing using AuNP / CNF membrane electrode in bulk The glucose sensor was used as the working electrode, counter electrode, and reference electrode, respectively, and amperometry (+0.6 V) was performed in 10 mL of 0.2 M phosphate buffer (pH 7.0) using a platinum mesh electrode and an Ag|AgCl electrode. A stirrer piece was placed in the cell and the mixture was stirred at 500 rpm. After the current stabilized, 25 mM glucose solution was added every minute to measure the change in current. The results are shown in Figures 11(A) and 11(B). Figure 11(A) is a graph of the current response when a glucose solution was added, and the figure in Figure 11(A) is a graph in which a part of Figure 11(A) is enlarged. Figure 11(B) is a graph in which the current value is plotted against the concentration based on the results of Figure 11(A), and the figure in Figure 11(B) is a Lineweaver-Burk double reciprocal plot.

[0098] As shown in Figure 11(A), when the glucose solution was added, the current rose quickly and showed a stable current response. This is thought to be because the hydrogen peroxide produced by the enzyme reaction was observed as a current response. In addition, as shown in Figure 11(B), the current value rose with an increase in glucose concentration, and the current response showed good concentration dependency in the glucose concentration range of 0.2 mM to 10 mM.

[0099] A glucose sensor using an AuNP / CNF membrane electrode was used to measure glucose concentrations at even lower concentrations (0.001 mM to 0.1 mM) to investigate the detection limit. Figure 12(A) is a graph of the current response when a glucose solution was added, and Figure 12(B) is a graph plotting the current value against the concentration based on the results of Figure 12(A). As shown in Figures 12(A) and 12(B), it was confirmed that the glucose sensor using the AuNP / CNF membrane electrode can measure concentrations down to a lower limit of 0.01 mM. In other words, it was confirmed that the measurement method using the glucose sensor using the AuNP / CNF membrane electrode can quantify a concentration range 10 times wider than the colorimetric method. From this, it is possible to quantify a wide concentration range without diluting the sample by using a glucose sensor using an AuNP / CNF membrane electrode, and it is expected to be applied to glucose sensing in various situations.

[0100] In addition, the current response to the concentration of the glucose sensor using the AuNP / CNF membrane electrode was plotted as a curve based on the Michaelis-Menten equation, which shows the enzyme reaction kinetics shown in the following formula (4), as shown in Figure 11(B). From the analysis of the linear plot, the Michaelis-Menten constant Km, which represents the affinity between the enzyme and the substrate, was calculated to be 5.6 mM. The Michaelis-Menten constant Km represents the affinity between the enzyme and the substrate, and a lower constant indicates a higher affinity. The value calculated this time was lower than the constants calculated using other glucose sensors (see Z. Cao, Y. Zou, C. Xiang, Li-Xian Sun, and F. Xu, Anal. Letters, 2007, 40, 2116, etc.), and it was confirmed that the sensor functions as a high affinity sensor. In addition, the porous structure of the AuNP / CNF membrane electrode enables a large electrochemically active surface and strong enzyme immobilization. It is presumed that the AuNP / CNF membrane functions as a porous electrode due to its numerous voids and particulate nature, and exhibits high enzyme activity. v=Vmax[S] / (Km+[S])...Equation (4) (In the formula, v: reaction rate, Vmax: maximum reaction rate, [S]: substrate concentration.)

[0101] Example 12 Evaluation of glucose sensor selectivity The glucose sensor was used as the working electrode, counter electrode, and reference electrode, respectively, and amperometry (+0.6 V) was performed in 10 mL of 0.2 M phosphate buffer (pH 7.0) using a platinum mesh electrode and an Ag|AgCl electrode. A stirrer piece was placed in the cell and stirred at 500 rpm. After the current stabilized, 100 μL each of 25 mM glucose solution, 20 mM sucrose solution, 20 mM acetic acid solution, 20 mM sodium chloride solution, 20 mM ascorbic acid solution, 20 mM urea solution, 20 mM lactic acid solution, and 100 mM glucose solution was added every minute to measure the change in current. The results are shown in Figure 13(A) and Figure 13(B). Figure 13(A) is a graph of the current response when each solution was added, and Figure 13(B) is a graph plotting the current value against the glucose concentration based on the results of Figure 13(A).

[0102] As shown in Figures 13(A) and 13(B), when interfering substances other than glucose were added, no change was observed in the current response, and the electrode responded only to glucose. It was confirmed that the AuNP / CNF membrane electrode with GOD immobilized exhibited high selectivity for glucose. In addition to glucose, sweat contains interfering substances such as lactic acid, cortisol, sodium ions, and chloride ions. Therefore, the glucose sensor using the AuNP / CNF membrane electrode can measure the glucose concentration without being inhibited by interfering substances contained in sweat.

[0103] Example 13 Glucose sensing in sweat A two-electrode cell 30 as shown in FIG. 14 was prepared by cutting out the AuNP / CNF film (gold: 13 vol.%). As shown in FIG. 14, a working electrode 32 (AuNP / CNF film electrode) and a counter electrode 33 were provided on a substrate 31 at a predetermined interval. GOD was then immobilized on the working electrode 32 in the same manner as in the preparation of the glucose sensor. 50 μL of phosphate buffer (pH 7.0) was dropped to cover both the working electrode 32 and the counter electrode 33, and the electrodes were covered with a cover glass 34. Amperometry was performed at a constant potential of +0.6 V, and a glucose solution was added when the current stabilized. The results are shown in FIG. 15(A) and FIG. 15(B). FIG. 15(A) is a graph of the current response when a glucose solution was added, and FIG. 15(B) is a graph in which the peak current value is plotted against the concentration based on the results of FIG. 15(A).

[0104] As shown in FIG. 15(A), an increase in the current value was confirmed with an increase in the glucose concentration. In addition, as shown in FIG. 15(B), a curve based on the Michaelis-Menten equation was drawn, showing good concentration dependency of the current response in the glucose concentration range of 0.01 to 20 mM. In the glucose concentration range of 0.001 to 0.007 mM, no current response according to the concentration was observed, and the detection limit of this glucose sensor was 0.01 mM. In addition, the Michaelis-Menten constants of the glucose sensors using the AuNP / CNF membranes prepared four times in the same way were all 5.0 to 5.6 mM. From this, it was found that the glucose sensor of the two-electrode cell using the AuNP / CNF membrane functions as a glucose sensor with high affinity between the enzyme and the substrate and has high reproducibility. In addition, when the glucose selectivity was evaluated, the plot against the glucose concentration showed the same value as the measurement result in bulk (glucose sensing using the AuNP / CNF membrane electrode in the bulk described above), and it was confirmed that the glucose sensor had the same reproducibility.

[0105] Example 14 Evaluation of glucose concentration in sweat after eating Sweat was collected under normal conditions and after a meal (0 to 120 minutes). The timing of sweat collection is shown in FIG. 16(A). Blood glucose levels depend on exercise intensity, and because glucose levels decrease when exercising to collect sweat, subjects were encouraged to sweat by bathing their feet in a foot bath, and sweat was collected. Amperometry was performed at a constant potential of +0.6 V using the glucose sensor. When the current was stabilized, the collected sweat was added. The results of amperometry using sweat before and after a meal are shown in FIG. 16(B). The broken line a in FIG. 16(C) is a graph in which the current level of sweat collected before a meal is shown as a dotted line, and the current value is plotted against the time elapsed after a meal.

[0106] Example 15 Evaluation of sweat glucose concentration based on exercise intensity The subjects walked 30 minutes after a meal, when blood glucose levels are at their highest, and sweat was collected 45 minutes after the meal. The glucose concentration was evaluated in the same manner as in the evaluation of glucose concentration in sweat after a meal. The results are shown as the line graph b in Figure 16(C).

[0107] As shown in Figures 16(B) and 16(C), the current level increased until 25 min after the meal, and then decreased to the original glucose level after 100 min. In addition, when the subjects exercised (walked) between 30 and 45 min after the meal, the current value was significantly decreased compared to when they did not exercise. These current response changes were consistent with the blood glucose levels expected in healthy humans. Therefore, it was confirmed that the glucose sensor using the AuNP / CNF membrane electrode can accurately measure the glucose concentration in sweat.

[0108] Example 16 (Fabrication of lactate sensor) Lactate oxidase derived from Aerococcus aeruginosa (hereinafter referred to as LOD) was immobilized on an AuNP / CNF membrane electrode by the glutaraldehyde crosslinking method. In conjunction with the immobilization, a mixture of GOD, bovine serum albumin (hereinafter referred to as BSA), and glutaraldehyde (hereinafter referred to as GA) was prepared. The method for preparing the mixture is as follows. (1) Set the LOD at a given concentration (14 UμL -1 ) and dissolved in 0.2 M phosphate buffer (pH 7.0) to prepare LOD solutions. (2) Weigh out approximately 11 mg of BSA and dilute it to 110 mg mL -1 A BSA solution was prepared by dissolving the BSA in 0.2 M phosphate buffer (pH 7.0) so that the concentration became (3) A GA solution was prepared by dissolving the 25% GA solution in 0.2 M phosphate buffer (pH 7.0) to a concentration of 7%. (4) 3 μL of the LOD solution from (1), 29 μL of the BSA solution from (2), and 4 μL of the GA solution from (3) were mixed to obtain a total of 36 μL of a mixed solution. 6 μL (7 U) of the mixed solution was dropped onto the AuNP / CNF membrane electrode (gold: 13 vol.%). The mixture was left to stand in the dark for 24 hours to obtain a lactate sensor. The prepared lactate sensor was then stored in 0.2 M phosphate buffer (pH 7.0).

[0109] Example 17 Lactic acid sensing in bulk using AuNP / CNF membrane electrode The lactate sensor was used as the working electrode, counter electrode, and reference electrode, respectively, and amperometry (+0.6 V) was performed in 10 mL of 0.2 M phosphate buffer (pH 7.0) using a platinum mesh electrode and an Ag|AgCl electrode. A stirrer piece was placed in the cell and the mixture was stirred at 500 rpm. After the current stabilized, 25 mM lactate solution was added every minute to measure the change in current. The results are shown in Figures 17(A) and 17(B). Figure 17(A) is a graph of the current response when lactate solution was added, and the figure in Figure 17(A) is a graph in which a part of Figure 17(A) is enlarged. Figure 17(B) is a graph in which the current value is plotted against the concentration based on the results of Figure 17(A), and the figure in Figure 17(B) is a Lineweaver-Burk double reciprocal plot.

[0110] As shown in FIG. 17(A), when the lactic acid solution was added, the current rose quickly and showed a stable current response. It is believed that this was because the hydrogen peroxide produced by the enzyme reaction was observed as a current response. Lactate oxidase reacts lactic acid with dissolved oxygen to produce pyruvic acid and hydrogen peroxide. As shown in FIG. 17(B), the current value rose with an increase in the lactic acid concentration, and the current response showed good concentration dependence in the lactic acid concentration range of 0.1 mM to 10 mM. From the analysis using a linear plot, the Michaelis-Menten constant Km was calculated to be 1.1 mM, confirming that the sensor functions as a high affinity sensor.

[0111] Example 18 Evaluation of lactate sensor selectivity The lactate sensor was used as the working electrode, counter electrode, and reference electrode, respectively, and amperometry (+0.6 V) was performed in 10 mL of 0.2 M phosphate buffer (pH 7.0) using a platinum mesh electrode and an Ag|AgCl electrode. A stirrer piece was placed in the cell and stirred at 500 rpm. After the current stabilized, 100 μL each of 25 mM lactate solution, 20 mM sucrose solution, 20 mM acetic acid solution, 20 mM sodium chloride solution, 20 mM ascorbic acid solution, 20 mM urea solution, 20 mM glucose solution, and 100 mM lactate solution was added every minute to measure the change in current. The results are shown in Figure 18(A) and Figure 18(B). Figure 18(A) is a graph of the current response when each solution was added, and Figure 18(B) is a graph plotting the current value against the lactate concentration based on the results of Figure 18(A).

[0112] As shown in Figures 18(A) and 18(B), when interfering substances other than lactate were added, no change was observed in the current response, and the sensor responded only to lactate. It was confirmed that the AuNP / CNF membrane electrode with the fixed LOD showed high selectivity for lactate. Therefore, the lactate sensor using the AuNP / CNF membrane electrode can measure the lactate concentration without being inhibited by interfering substances contained in sweat.

[0113] Example 19 Lactate sensing using AuNP / CNF membrane electrode during exercise The lactate concentration in sweat is more than 10 times that in blood. It is said that the lactate concentration increases with increasing exercise intensity, and the lactate content in sweat of healthy people increases from 4-25 mM at rest to 50-80 mM. For this reason, in order to measure the lactate concentration in sweat without diluting the sweat, it is required to be able to measure samples with a concentration of at least 50 mM. Therefore, it is necessary to expand the measurable concentration range of this lactate sensor to higher concentrations. Therefore, the number of LOD units fixed to the AuNP / CNF membrane electrode was increased, and the current response with the addition of lactate was evaluated. That is, in the preparation of the above lactate sensor, lactate of three different concentrations (14 UμL -1 , 28UμL -1 , or 42 UμL -1) LOD solutions were prepared. The number of LOD units immobilized on the AuNP / CN membrane electrode was 7U, 14U, or 21U, respectively. Measurements were performed in the same manner as in the lactate sensing using the AuNP / CNF membrane electrode in bulk described above. The results are shown in Figures 19(A) and 19(B). Figure 19(A) is a graph of the current response when a lactate solution was added. Figure 19(B) is a graph in which the current value is plotted against the concentration based on the results of Figure 19(A).

[0114] As shown in Figures 19(A) and 19(B), the current value for the lactate concentration increased with an increase in the number of LOD units immobilized on the AuNP / CNF membrane electrode. This confirmed that the upper limit of the measurable concentration range can be expanded by increasing the number of LOD units immobilized on the AuNP / CNF membrane electrode. Therefore, the lactate sensor using the AuNP / CNF membrane electrode can be used to monitor the lactate level in sweat.

[0115] Example 20 <Changes in resistance due to human body movement> The AuNP / CNF film (gold: 13 vol.%) was moistened with a small amount of water and attached to the palm. Figure 20(A) is a photograph of the AuNP / CNF film attached to the palm. A gold wire was connected to the AuNP / CNF film as a lead wire. The resistance value of the AuNP / CNF film was measured with a digital multimeter (34410A, Agilent Technologies, applied current: 1 mA) when the palm was opened and closed every second to represent the movement of the human body. The results are shown in Figure 20(B).

[0116] As shown in Figure 20(A), it was confirmed that the AuNP / CNF film adhered to the skin when pressed against the palm. Furthermore, it was confirmed that the AuNP / CNF film adhered closely to the unevenness of the skin, did not peel off due to palm movement, and remained attached to the palm. Furthermore, as shown in Figure 20(B), there was almost no change in resistance value due to opening and closing the hand, which was within the range of error of the measurement value (2.0 Ω or less), and stable conductivity was maintained. From these findings, it was confirmed that the AuNP / CNF film can flexibly respond to the movement of the human body, and its conductivity with respect to state changes is not affected by the movement of the human body and is sufficiently stable.

[0117] Example 21 <Body fat percentage measurement using AuNP / CNF membrane> The AuNP / CNF film (gold: 13 vol.%) was attached to the heels of both feet of the subjects, and the subjects (1 to 3) were placed in a standing position on the ground. The AuNP / CNF film was connected to an AC power supply (IM6, manufactured by ZAHNER-Elektrik), and a sine wave current of 50 kHz and 1.0 mA was applied to measure the impedance. The body fat percentage was calculated according to the following calculation method based on the obtained impedance and the height and weight of the subjects. Body density (BD) was calculated from the subject's height (Ht), weight (W), and impedance (BI) using equation (5).Then, the body density (BD) was substituted into Brozek's equation (equation (6)) to calculate the body fat percentage. BD [g cm -3 ]=1.1278-0.115×W×BI / Ht 2 +0.000095·BI···Equation (5) Body fat percentage [%]=(4.971 / BD-4.519)×100...Equation (6) (In the formula, W: body weight [kg], BI: impedance [Ω], Ht: height [cm].) The body fat percentage was measured using a commercially available body composition analyzer (HBF-361, manufactured by Omron Corporation) and compared with the results obtained using the AuNP / CNF membrane. The results are shown in Table 1. In the body fat percentages (%) shown in Table 1, A is the measurement result of the body fat percentage using the AuNP / CNF membrane of the present invention, and B is the measurement result of the body fat percentage measured using the commercially available body composition analyzer.

[0118] [Table 1]

[0119] As shown in Table 1, when comparing the results of body fat percentage measurements using the AuNP / CNF membrane with those measured using a commercially available body composition analyzer, it was confirmed that similar trends were observed in both.

[0120] Example 22 <Preparation of three-electrode cell> As shown in FIG. 24, a three-electrode cell was prepared using an AuNP / CNF membrane electrode (gold: 13 vol.%) as the working electrode, an AgNP / CNF membrane electrode (silver: 20 vol.%) as the reference electrode, and an AuNP / CNF membrane electrode (gold: 13 vol.%) as the counter electrode. -1 Cyclic voltammetry (CV) measurements were performed at a sweep rate of 1000 s. The three-electrode cell did not function as an electrolytic cell in a dry state without the addition of electrolyte, and measurements were not possible. In the three-electrode cell, the CNF membrane was immersed in a 5 wt% Nafion (Chemourus) solution, arranged to cover the working electrode, part of the counter electrode, and the reference electrode as shown in Figure 22, and dried at 60 °C for 30 minutes to form a solid electrolyte membrane. Even in a dry state without the addition of electrolyte, the Nafion membrane contains equilibrium moisture with the humidity of the atmosphere, and the polar groups of Nafion are ionized and act as an electrolyte, so a current response to voltage was observed. The results of the CV measurements are shown in Figure 25.

[0121] Example 23 <Preparation of three-electrode cell> A 0.1 M KCl aqueous solution containing 10 mM K3[Fe(CN)6] was prepared as an electrolyte. As shown in Figure 24, 200 μL of the electrolyte was dropped to cover a three-electrode cell consisting of an AuNP / CNF membrane electrode (gold: 13 vol.%) as the working electrode, an AgNP / CNF membrane electrode (silver: 20 vol.%) as the reference electrode, and an AuNP / CNF membrane electrode (gold: 13 vol.%) as the counter electrode. -1 The CV measurement was performed at a sweep rate of 50 mVs. The CNF membrane was immersed in a 5 wt% Nafion (Chemourus) solution, arranged so that it covered the working electrode, part of the counter electrode, and the reference electrode, and dried at 60 °C for 30 minutes to form a solid electrolyte membrane. As above, 200 μL of the electrolyte was dropped, and the voltage was measured at 50 mVs. -1 CV measurements were performed at a sweep rate of 100 Hz. In both cases, [Fe(CN)6] 3- A current response was observed accompanying the oxidation and reduction of the electrode, and the cell functioned as an electrode. The results of the CV measurements are shown in FIG. [Explanation of symbols]

[0122] 10 Body fat percentage measuring device 11 Composite membrane 12 AC power supply 13 Impedance measurement section 20,50 Sensor element 22,221,222,223 Molecular recognition body 23 void 24 Substrate 30 Two-electrode cell 31 Base material 32 Working electrode 33 Opposite 34 Coverslip 51 Flat electrode

Claims

1. A composite membrane comprising conductive nanoparticles and nanofibers, The nanofibers have a plurality of voids between them that communicate with the outside, the conductive nanoparticles are attached to a surface of the nanofiber and are present in the plurality of voids; The nanofibers are hydrophilic and biocompatible; The composite film is electrically conductive, has a total reflectance of less than 50% of that of a pure metal foil, and is used by being directly attached to and in close contact with a contact object that has been subjected to a hydrophilic treatment or that contains moisture; The composite membrane is capable of achieving a moisture content of 2.5 times its dry weight; The composite membrane has a resistance change of 0.5 Ω or less due to an increase or decrease in the amount of liquid present in the plurality of voids.

2. 2. The composite membrane according to claim 1, wherein the amount of the conductive nanoparticles is 2.0 to 20 vol. % relative to the total amount (100 vol. %) of the conductive nanoparticles and the nanofibers.

3. The composite membrane of claim 1 or 2, wherein the nanofibers comprise cellulose.

4. The composite film of any one of claims 1 to 3, wherein the conductive nanoparticles comprise a metal, a metal oxide, or carbon.

5. The composite membrane according to any one of claims 1 to 4, wherein the composite membrane has a tensile strength of 0.5 to 100 MPa.

6. 6. The composite membrane according to claim 1, wherein the contacted object is skin or tissue inside a living body.

7. The composite membrane of any one of claims 1 to 5, wherein the contacted body comprises metal, glass, plastic, ceramic, or carbon.

8. The composite film has flexibility such that it deforms or expands in accordance with the movement of the human body when attached to the human body, and the change in resistance value due to the movement of the human body is 2.0 Ω or less. The composite membrane according to any one of claims 1 to 7.

9. A composite membrane according to any one of claims 1 to 8; A molecular recognition body disposed in the plurality of voids; A sensor element comprising:

10. 10. The sensor element according to claim 9, wherein the molecular recognition entity comprises an enzyme, an antibody, a DNA or RNA containing an aptamer, an artificial antibody formed from a molecularly imprinted polymer, or an ion-selective molecule.

11. The sensor element according to claim 10 , wherein the enzyme comprises an oxidase, a reductase, or a dehydrogenase.

12. The sensor element according to claim 11 , wherein the oxidase comprises glucose oxidase or lactate oxidase.

13. The sensor element according to claim 11 , wherein the dehydrogenase comprises glucose dehydrogenase or lactate dehydrogenase.

14. A wearable measurement device comprising the sensor element according to any one of claims 9 to 13.

15. A body fat percentage measuring device comprising the composite membrane according to any one of claims 1 to 8.

16. An electrochemical cell device comprising the composite membrane according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Inorganic fine particle-containing composition and coating using the same

    JP2013249448A

  • Analytical sensor and its manufacturing

    JP2015525878A

  • Cell for measurement, detector, and analyzer

    JP2016208883A

  • Composite planar body and method for producing the same, and member having the same formed thereon

    JP2018154921A

  • Nanocomposite films with conducting and insulating surfaces

    US20170103826A1